Poppy done to death ebook An aurora teagarden mystery. - Harris, Charlaine (Aurora Teagarden, 2016)
From the #1 New York Times bestselling author of the books that inspired True Blood on HBO and Midnight, Texas on NBC, Poppy Done to Death forms the basis of Reap What You Sew , an Aurora Teagarden movie on the Hallmark Movies and Mysteries Channel Aurora Teagarden, mild-mannered librarian, has spent her entire life in the same small Georgia town. Along with her sister-in-law Poppy, Roe has finally earned a coveted spot in the Uppity Women, an exclusive group that does more than flower arranging. But Poppy is a no-show on their induction day. Roe stops by Poppy's house to find out why and is shocked to discover Poppy dead on the kitchen floor, and it's not by accident. There's no lack of suspects, since both Poppy and her husband were unfaithful. Even the detective in charge of the case, Roe's former lover Arthur Smith, has a past with Poppy. As if that weren't enough, Roe has rekindled a relationship with another old flame and things are moving fast, with plans to meet his mother at Thanksgiving. She's also acquired an unexpected house guest: her half-brother, who's run away from his parents' home in California. Balancing her personal life while looking into Poppy's murder isn't easy, but Roe is determined to give it — and Poppy — her best effort. And when Roe discovers that the crime scene has been ransacked, she knows someone is desperate to hide a secret. Roe will have to dig through Poppy's life to uncover the truth and bring the killer to justice. Poppy Done to Death is the engaging eighth installment of the Aurora Teagarden mysteries by #1 New York Times bestselling author Charlaine Harris. The series has been adapted into film for Hallmark Movies & Mysteries.